THE IMPORTANCE OF AUGMENTED REALITY (AR) MEDIA TO INCREASE INTEREST IN LEARNING AT PRIMARY SCHOOLS - Nunung Alya Ayu Lastari; Donna Boedi Maritasari; Muhammad Husni; Ika Wardina; Asri Nofita Sari (Universitas PGRI Palembang, 2023)
A response to the transformation in education is learning media. In order to adapt to changes in education, learning media innovation is a calculated move. Increasing student engagement and learning outcomes is influenced by the continuous development of educational media. It is expected that the integration of Augmented Reality (AR) technology into natural science instruction will improve scientific literacy, especially for elementary school pupils. Three-dimensional media makes the approach more flexible, engaging, and creative by using different items as target markers. Investigating and evaluating the use of Augmented Reality (AR) media in elementary school natural science instruction is the goal of this project. A literature review is the research methodology used, and data gathering is done using a literature study strategy. Learning outcomes and student attention have been demonstrated to be greatly enhanced by the development and application of augmented reality (AR) media in a variety of natural scientific courses. Among these subjects are the diets of animals, ecosystems, plants, and animals that go through full metamorphosis. Students are able to develop their creative faculties, assess their emotional intelligence, and grow more cooperative and competitive with their peers as a result.